Do you hear what I hear?: A comparison of police officer and civilian fairness judgments through procedural justice - Hazen, Katherine P. (Psychology, crime & law, 2022)
Procedural justice theory posits that people care at least as much about how a decision was made as they do about the outcome. Although policymakers and researchers argue that procedural justice-based interventions can improve police-civilian interactions, little research has examined how authorities evaluate decision-making processes. This research examined whether police officers and civilians evaluate fairness in police-civilian encounters through the same mechanisms. 69 police officer and 113 civilian participants, recruited through Qualtrics professional panels and Amazon’s Mechanical Turk respectively, read a vignette describing a police-civilian interaction in which the civilian explained why they violated the law (procedural justice) or were interrupted by the officer (procedural injustice) and made evaluations of the interaction. Multiple-group analyses using bootstrapping revealed that both police officers and civilians rated the procedural justice condition as more fair because they rated the officer as more respectful and trustworthy and because they perceived the civilian had more voice than in the procedural injustice condition. Further, direct and indirect pathways through respect were not present when police officer pathways were allowed to vary, suggesting police may rely on social information differently than civilians.